(untitled) (Agro Productividad, 2025)
Objective: To determine the prevalence of mastitis and estimate the economic losses caused by the disease in dual-purpose livestock units in Cuajinicuilapa, Guerrero, Mexico. Design/Methodology/Approach: A total of 261 cows were sampled, encompassing 1,025 mammary quarters. The California Mastitis Test (CMT) was used for diagnosing mastitis, and economic losses were estimated based on milk production loss according to the severity of the disease. Results: The overall prevalence was 42.9%, with 40.2% corresponding to subclinical mastitis and 2.7% to clinical mastitis. Among the quarters sampled, 80% tested negative, 17.5% showed subclinical mastitis, 0.7% presented clinical mastitis, and 1.8% were classified as blind quarters. Economic losses associated with mastitis ranged from USD 0.248 to USD 1.253 per day. Study Limitations/Implications: The lack of record-keeping in the Livestock Production Units (LPU) studied hindered the estimation of additional costs related to the presence of mastitis. Findings/Conclusions: The prevalence of mastitis in dual-purpose LPUs in Cuajinicuilapa, Guerrero, was lower compared to other regions of the country. Subclinical mastitis was more frequent, leading to economic losses across all herds due to reduced income from milk sales. These losses often go unnoticed by producers, given the asymptomatic nature of subclinical cases.